Analyzing Impact of Demographic Processes on Education System in the Republic of Tyva - E. A. Dolgikh; L. A. Davletshina (Вестник Российского экономического университета имени Г. В. Плеханова, 2025)
The article provides characteristics of the Republic of Tyva in view of nature and climate conditions and level of social and economic development of the entity. Special attention is paid to researching demographic processes taking place in the Republic with regard to the national project and regional state program dealing with the problem of education. Results of the statistic analysis show that average annual population of the republic increased in 2022 in comparison with 2012. The major part of the population lived in urban areas in this period of time. More than a third of the population is younger than employable age. Availability of people at the age below 15 forms educational potential of the region necessary to resolve problems of academic and professional personnel training and market of highlyqualified specialists, who could contribute to the development of different industries of economy, education and state structures of Tyva. The level of difference of population structures by age groups in the Russian Federation was estimated by calculating integral factors of structural shifts. Education institutions of the Republic were characterized by education level. It was found that the growth in the number of learners requires new places and more personnel.